The Utilization of the Design Application for Arabic Learning - Frananda, Angga; Werry, Tehn; Wais, Anne (Journal International of Lingua and Technology, 2023)
The purpose of this study was to describe the use of the Canva application as an effort to increase students' interest in learning Arabic. This research uses a library research method. The sources of this literature are journals and books similar to this research. One of the learning developments can be in the form of e-modules. And this can be done using the Canva app. The Canva application is one of the online applications that can be free or paid. This application can also be used to design learning media with several interesting templates, the presentation of shapes, images, colors, and letters also has many variations. How to use this application is to create a Canva account, design, choose a background, edit the background, add text, and lastly, download or share text. By using this Canva application, students can create more interesting Arabic teaching materials. Therefore, through e-modules, Arabic subjects are interesting so that they can strengthen students' learning interest in distance learning and also not boring